2002
DOI: 10.1039/b208013c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photophysics of a linear non-covalently linked porphyrin–fullerene dyad

Abstract: The synthesis and characterization of a new pyridinofullerene ligand capable of forming axially symmetric complexes with ZnTPP is reported; molecular modelling studies, 1H NMR, UV-Vis spectroscopy and fluorescence quenching data support formation of a strong complex between the new ligand and ZnTPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 11 publications
3
54
0
Order By: Relevance
“…One singlet for the pyrrolidine ring protons and two different quartets and triplets for the methylene and methyl groups on the malonate belt clearly indicate a D 2h symmetry for compound 2, that is, all the addends are located at octahedral positions (trans-1 bis(pyrrolidine) and equatorial malonate moieties). In addition, 30 sets of equivalent carbon signals in the 13 C NMR spectrum are consistent with the proposed D 2h symmetry of compound 2 (see the Supporting Information). In the case of compound 9, three quartets with a ratio of 1:1:2 were observed at d = 4.24-4.28, 4.29-4.33, 4.34-4.37 ppm for the methylene groups of the malonate adducts, consistent with the symmetry of the compound.…”
Section: Synthesis Of 2 Andsupporting
confidence: 70%
See 4 more Smart Citations
“…One singlet for the pyrrolidine ring protons and two different quartets and triplets for the methylene and methyl groups on the malonate belt clearly indicate a D 2h symmetry for compound 2, that is, all the addends are located at octahedral positions (trans-1 bis(pyrrolidine) and equatorial malonate moieties). In addition, 30 sets of equivalent carbon signals in the 13 C NMR spectrum are consistent with the proposed D 2h symmetry of compound 2 (see the Supporting Information). In the case of compound 9, three quartets with a ratio of 1:1:2 were observed at d = 4.24-4.28, 4.29-4.33, 4.34-4.37 ppm for the methylene groups of the malonate adducts, consistent with the symmetry of the compound.…”
Section: Synthesis Of 2 Andsupporting
confidence: 70%
“…In 2003, Wilson et al prepared a pyridinofulleropyrroline derivative (1) which exhibited effective electronic coupling between the C 60 core and the pyridyl nitrogen atom, as confirmed by 1 H NMR spectroscopy, molecular modeling studies, UV-visible spectroscopy, and fluorescent-quenching experiments (Scheme 2). [13] Electrochemical studies further confirmed this effective coupling between the pyridyl nitrogen atom and the fullerene core based on the fact that the first reduction of the C 60 core was shifted by 40 mV upon complexation with a Zn-porphyrin derivative. [14] Thus C 60 hexakis-adducts 2 and 3 with terpyridyl or pyridyl groups in the trans-1 positions and the corresponding trans-1 bis-adducts 4 and 5 (Scheme 3) were selected as the synthetic targets in the present work.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations